2017
DOI: 10.1155/2017/9820181
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Challenges of mTOR Inhibitors Use in the Treatment of Patients with Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex (TSC) is a genetic condition characterized by the presence of benign, noninvasive, and tumor-like lesions called hamartomas that can affect multiple organ systems and are responsible for the clinical features of the disease. In the majority of cases, TSC results from mutations in the TSC1 and TSC2 genes, leading to the overactivation of the mammalian target of rapamycin (mTOR) signalling pathway, which controls several cell functions, including cell growth, proliferation, and surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 75 publications
0
38
0
Order By: Relevance
“…Our control docking is also validated with a similar binding site which has been reported earlier [ 55 ]. It is suggested that the shared macrolide structure between rapamycin and everolimus permits interaction with FKBP5, subsequently to be selective to inhibit mTORC1 over mTORC2 [ 56 ]. It was observed that both of these triterpenoid compounds (asiaticoside and asiatic acid) bound at the similar binding region as everolimus, indicating a similar potential for the mTOR kinase inhibition activity ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our control docking is also validated with a similar binding site which has been reported earlier [ 55 ]. It is suggested that the shared macrolide structure between rapamycin and everolimus permits interaction with FKBP5, subsequently to be selective to inhibit mTORC1 over mTORC2 [ 56 ]. It was observed that both of these triterpenoid compounds (asiaticoside and asiatic acid) bound at the similar binding region as everolimus, indicating a similar potential for the mTOR kinase inhibition activity ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to its varying effect on mTOR inhibition with variation in dosage (Rivera et al, 2011 ). However, no reactivation of latent Mtb infection has been reported in these studies (Huang et al, 2015 ; Palavra et al, 2017 ).…”
Section: Mtor Inhibitors As Potential Hdt For Tbmentioning
confidence: 88%
“…In a phase I clinical trial with 87 ER + /high-proliferative breast cancer cases, majority of patients treated with ridaforolimus demonstrated reduced tumor activity (Di Cosimo et al, 2015 ). Similarly, a phase II clinical trial showed promising results for ridaforolimus to treat patients with endometrial, soft tissue and bone cancers (Palavra et al, 2017 ). The effect of ridaforolimus on cell metabolism and growth is largely dependent on the dose of drug used for treatment.…”
Section: Mtor Inhibitors As Potential Hdt For Tbmentioning
confidence: 99%
“…Patients who have not developed cerebral anatomical lesions and any neurological symptom by fi ve years have a favorable intellectual prognostic [3] and cases with the presence of cardiac rhabdomyomas without signifi cant neurological lesions [22,30,31]. However, a worse neurological prognosis of the mutations in TSC2 has been documented, with a higher percentage of drug-resistant epilepsy, more severe cognitive retardation, a higher frequency of behavioral disturbances and a greater load of NMR lesions, as well as other neuropsychiatric disorders [1,31] and in cases with association with Systemic Lupus Erythematosus [32,33].…”
Section: Casementioning
confidence: 99%